2010
DOI: 10.1007/s00296-010-1506-2
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine reduces invasion and migration ability in fibroblast-like synoviocytes cells co-cultured with activated human monocytic THP-1 cells by inhibiting the expression of MMP-2, MMP-9, CD147

Abstract: CD147 expressed by monocytes, macrophages, and synoviocytes cells can stimulate the production of matrix metalloproteinases (MMPs) associated with the development of rheumatoid arthritis (RA). We investigated the effects of Sinomenine (SIN) on invasion and migration ability and gene expression of CD147, MMP-2, MMP-9 of fibroblast-like synoviocytes cells (FLS) co-cultured with activated human monocytic THP-1 cells (A-THP-1) in vitro. SIN is a pure alkaloid extracted from the Chinese medical plant Sinomenium acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Additionally macrophages produce a spectrum of proteases (in addition to uPA) such as matrix metalloproteinases that drive tissue destruction in RA. [30][31][32] In CIA, macrophages play a preeminent role in driving disease. Targeting molecules that promote macrophage proliferation, accumulation or activation (eg, CSF-1, granulocytemacrophage colony-stimulating factor, TNF-a, IL-1b, and IL-6) [33][34][35][36][37][38][39][40] suppresses CIA in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally macrophages produce a spectrum of proteases (in addition to uPA) such as matrix metalloproteinases that drive tissue destruction in RA. [30][31][32] In CIA, macrophages play a preeminent role in driving disease. Targeting molecules that promote macrophage proliferation, accumulation or activation (eg, CSF-1, granulocytemacrophage colony-stimulating factor, TNF-a, IL-1b, and IL-6) [33][34][35][36][37][38][39][40] suppresses CIA in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also confirmed that hyperoside reduced the LPS-induced increase in production of TNFα, IL-1β, and IL-6 Over 20 members of the MMP family have been identified in humans to date. Elevated gene expression of MMPs is critical for the progression of RA [47,48] . LPS can stimulate FLS to secrete MMPs, and this induction is regulated at the transcriptional and translational levels [49] .…”
Section: Discussionmentioning
confidence: 99%
“…When orally administered at the doses of 100 and 300 mg/kg, SIN could attenuate adjuvantinduced arthritis (AIA) in rat and collagen-induced arthritis (CIA) in mouse through suppressing the production of autoantibody and modulating Th1/Th2 response (Feng et al, 2007;Mu et al, 2013). In vitro mechanistic studies showed that SIN could suppress the activation of T lymphocytes, induce the apoptosis of macrophage, reduce antigen-induced activation of basophils, and hinder migration of synoviocytes at concentrations over 0.5 mM (He et al, 2005;Huang et al, 2008;Liu et al, 1994;Ou et al, 2011). Overall, the minimal effective concentration of SIN against immunity or inflammation effector cells is quite high.…”
Section: Introductionmentioning
confidence: 99%